Effect of biostimulants and biofertilizers on soil properties, plant growth and flowering of rose cv. Rose Sherbet - RACHANA , L.; RAO, V.K. (Journal of Ornamental Horticulture, 2025)
The present investigation was carried out at Model Floriculture Centre, G. B. Pant University of Agriculture and Technology, Pantnagar, Udham Singh Nagar Uttarakhand. The experiment was laid out in RBD with nine treatments viz., T1 (100% Recommended dose of fertilizers- RDF), T2 (RDF 75% + Fulvic acid), T3 (RDF 50% + Fulvic acid), T4 (RDF 75% + Humic acid), T5 (RDF 50% + Humic acid), T6 (RDF 75% + Sea weed extract-IFFCO Sagarika), T7 (RDF 50% + Sea weed extract-IFFCO Sagarika), T8 (RDF 75% + IIHR- Arka microbial consortium) and T9 (RDF 50% + IIHR- Arka microbial consortium) and three replications. Among all the treatments plant height (63.53 cm), plant spread (55.57 cm), were found maximum in plants treated with humic acid @ 3 mL L–1 and 75% Recommended dose of fertilizers (RDF) i.e. T4 after 150 days of application. T4 also exhibited maximum leaf area per plant (1023.75 cm2), early flower bud appearance (31.47 days), maximum number of flowering shoots per plant per month (3.8), number of flowers per plant per month (18.13) and flower yield per plant per hectare (5693.17 Kg) were also enhanced by T4 whereas lowest values were noticed in T9 (Arka microbial consortium + 50% RDF). Among all the treatments the available N (191.30 kg ha–1), P (25.76 kg ha–1), K (178.08 kg ha–1) in soil, N (2.00%), P (0.40%), K (1.44%) content in plants and soil's bacterial population (2.373× 105 CFU) were enhanced by T4.